Plant–Agrobacterium interaction mediated by ethylene and super-Agrobacterium conferring efficient gene transfer - Nonaka, Satoko; Ezura, Hiroshi (Frontiers in Plant Science, 2014)
Agrobacterium tumefaciens has a unique ability to transfer genes into plant genomes. This ability has been utilized for plant genetic engineering. However, the efficiency is not sufficient for all plant species. Several studies have shown that ethylene decreased the Agrobacterium-mediated transformation frequency. Thus, A. tumefaciens with an ability to suppress ethylene evolution would increase the efficiency of Agrobacterium-mediated transformation. Some studies showed that plant growth-promoting rhizobacteria (PGPR) can reduce ethylene levels in plants through 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, which cleaves the ethylene precursor ACC into α-ketobutyrate and ammonia, resulting in reduced ethylene production. The whole genome sequence data showed that A. tumefaciens does not possess an ACC deaminase gene in its genome. Therefore, providing ACC deaminase activity to the bacteria would improve gene transfer. As expected, A. tumefaciens with ACC deaminase activity, designated as super-Agrobacterium, could suppress ethylene evolution and increase the gene transfer efficiency in several plant species. In this review, we summarize plant–Agrobacterium interactions and their applications for improving Agrobacterium-mediated genetic engineering techniques via super-Agrobacterium.